1989
DOI: 10.1037/0022-006x.57.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Changes in food intake and activity after quitting smoking.

Abstract: Quitting smoking often results in weight gain. The causes of the gain are not known. The present study evaluated changes in calories, total sugars, sucrose, fat, protein, and nonsugar carbohydrates as well as changes in activity levels after quitting smoking. Ninety-five subjects were randomly assigned to either early (Week 2) or late (Week 6) quit dates. Subjects were assessed on weight, food intake, activity levels, and smoking levels at baseline, at Weeks 4 and 8, and at Weeks 12 and 26 postquit. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
86
3
1

Year Published

1990
1990
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(97 citation statements)
references
References 34 publications
7
86
3
1
Order By: Relevance
“…For instance, in one recent study involving carefully monitored food ingestion during a well controlled smoking cessation program, quit dates were randomly assigned early and later in the program. Corresponding to each quit date there was a significant increase in calorie intake, and particularly increased ingestion of sucrose and fats (Hall, McGee, Tunstall, Duffy & Benowitz, 1989). In the present research, the interchangeability hypothesis is based on the assumption that sugar snacking and smoking influence energy and tension states, and there is evidence that this is the case.…”
mentioning
confidence: 69%
“…For instance, in one recent study involving carefully monitored food ingestion during a well controlled smoking cessation program, quit dates were randomly assigned early and later in the program. Corresponding to each quit date there was a significant increase in calorie intake, and particularly increased ingestion of sucrose and fats (Hall, McGee, Tunstall, Duffy & Benowitz, 1989). In the present research, the interchangeability hypothesis is based on the assumption that sugar snacking and smoking influence energy and tension states, and there is evidence that this is the case.…”
mentioning
confidence: 69%
“…Findings accord with the premise that nicotine deprivation increases the reward value of appealing carbohydrate snacks for female smokers. The increased reward value of snacks during nicotine withdrawal parallels and may help to explain the heightened intake of energy generally and carbohydrate treats particularly that has been documented among smokers undergoing nicotine withdrawal (Klesges et al, 1989;Spring et al, 1991;Hall et al, 1989) and that contributes to postcessation weight gain (Hall et al, 1989;Stamford et al, 1986). Lack of evidence that carbohydrates or sweets become more palatable after smoking discontinuation (Perkins et al, 1990;Redington, 1984;Rodin, 1987) has made it difficult to explain why snacking increases after nicotine withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…Because our observation period was restricted to the first 48 h after nicotine withdrawal, our findings do not indicate whether the increased reward value of carbohydrate snacks is transitory or longer lasting. However, a long-lasting effect appears likely based on the observations that (a) overeating of carbohydrates persists for at least 1 month after quitting smoking Hall et al, 1989); (b) the initial increase in calorie intake predicts weight gain 6 months after quitting (Hall et al, 1989); and (c) weight gain continues for at least 6 months postcessation (Hall et al, 1986) if not for several years (Williamson et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The present study focused on sweet taste because of the research relating nicotine administration/cigarette smoking with changes in consumption patterns of sweet-tasting, high caloric foods (Grunberg, 1982;Grunberg and Morse, 1984;Grunberg et al, 1985;Hall et al, 1989). Whether the decreased sucrose detection thresholds in current smokers would affect perception of sweetness when sucrose levels are above threshold (i.e., suprathresholds) or whether this decreased sensitivity can be partially reversed following long periods of smoking cessation, like that recovery observed for smell identification (Frye et al, 1990) and bitter taste sensitivity (Peterson et al, 1968) remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term nicotine exposure decreases (Grunberg, 1982), whereas abstinence from smoking (Hall et al, 1989;Perkins et al, 1990;Spring et al, 1991) or cessation of nicotine treatment in animals chronically exposed to nicotine (Grunberg et al, 1985) increases, consumption of palatable, particularly sweet-tasting, foods. Moreover, epidemiological data on per capita consumption patterns in the United States revealed that when cigarette consumption is high, sugar consumption is low and vice versa (Grunberg and Morse, 1984).…”
mentioning
confidence: 99%